2017
DOI: 10.2105/ajph.2016.303603
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Prevention Trial of Alcohol Use Among American Indian and White High School Students in the Cherokee Nation

Abstract: CMCA and CONNECT are effective interventions for reducing alcohol use among American Indian and other youths living in rural communities. Challenges remain for sustaining intervention effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 23 publications
1
58
0
1
Order By: Relevance
“…Also, we did not find positive changes in the hypothesized intermediate outcomes of alcohol expectancies, social support, or parent communication. Despite the lack of change through these intermediate pathways, the CONNECT intervention was effective at reducing alcohol use and alcohol‐related consequences . Perhaps CONNECT worked through other key pathways or through mechanisms unique to the intervention (ie, MI).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, we did not find positive changes in the hypothesized intermediate outcomes of alcohol expectancies, social support, or parent communication. Despite the lack of change through these intermediate pathways, the CONNECT intervention was effective at reducing alcohol use and alcohol‐related consequences . Perhaps CONNECT worked through other key pathways or through mechanisms unique to the intervention (ie, MI).…”
Section: Discussionmentioning
confidence: 96%
“…The combination of the 2 interventions had a similar effect as each intervention alone. Details of the trial design and alcohol use outcomes are described elsewhere . This article will describe the specific characteristics and implementation of the CONNECT SBI intervention, the universally‐implemented, multiculturally‐appropriate school‐based prevention program.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the prevention trial in the Cherokee Nation, the theory of community change was explicitly tested and defined as a process of citizen-led and direct-action community organizing (Komro et al, 2015, 2017). The direct-action community organizing process was the standard intervention delivered across communities, yet specific intervention components and their dosage varied based on local contexts (Komro et al, 2017). We hired local citizens to serve as community organizers and provided ongoing training and support in community organizing processes and strategies.…”
Section: Intervention Designmentioning
confidence: 99%
“…We conducted a community-randomized trial testing two theoretically distinct alcohol preventive interventions in rural towns within the jurisdictional service boundaries of the Cherokee Nation (Komro et al, 2015, 2017). We implemented a community environmental change intervention using community organizing called Communities Mobilizing for Change on Alcohol (CMCA) and a universally implemented individual-level intervention implemented within schools combining brief intervention with motivational interviewing called CONNECT and found that both interventions, alone and in combination, were effective in reducing past month alcohol use, heavy use, and alcohol consequences (Komro et al, 2017). Results of these preventive intervention trials conducted over the past two decades shape the prevention landscape in the United States, advancing theory, practice, and methods.…”
mentioning
confidence: 99%